Estuarine Subaqueous Soil Organic Carbon Accounting: Sequestration and Storage. Issue 2 (26th January 2015) - Millar, Christina M.; Owusu Aduomih, Adiza Ama; Still, Brett; Stolt, Mark H.
Abstract : Subaqueous soils have largely been overlooked in soil C accounting studies. Recent work suggests that shallow, subtidal soils along the Atlantic Coast contain soil organic C (SOC) pools that are equal to or greater than comparable upland pools. In this study, we investigated the spatial relationships between SOC pool size and subaqueous soil landscape units in three coastal lagoons in Rhode Island and estimated SOC sequestration rates for these soils. Fifty‐two pedons were sampled to 1 m and analyzed for SOC content and bulk density to calculate SOC pools. Pools varied significantly among soil landscape units and subaqueous soil Great Groups. Average SOC pools for the upper meter ranged from 354 Mg C ha −1 in mainland cove units (which frequently contained buried organic horizons) to 31 Mg C ha −1 in washover fan flat units. Soil organic C pool averages per Great Group ranged from 174 Mg C ha −1 in Sulfiwassents to 40 Mg C ha −1 in Psammowassents. Average sequestration rates ranged from 0.18 to 1.45 Mg C ha −1 yr −1 and were significantly different among soil landscape units. Subaqueous SOC pools and sequestration rates were found to be essentially equivalent to regional forest subaerial mineral soils. These data suggest that estuarine subaqueous soils may be important C sinks and should be included in sequestration studies of estuarine ecosystems. Furthermore, subaqueous soil surveys provide the spatial information needed for SOC accounting of coastal soils.